A Rare Deep-Rooting D0 African Y-Chromosomal Haplogroup and Its Implications for the Expansion of Modern Humans Out of Africa. Issue 4 (13th June 2019) - Haber, Marc; Jones, Abigail L; Connell, Bruce A; Asan,; Arciero, Elena; Yang, Huanming; Thomas, Mark G; Xue, Yali; Tyler-Smith, Chris
Abstract: Humans expanded out of Africa 50, 000-70, 000 years ago, but many details of this migration are poorly understood. Here, Haber et al. sequence Y chromosomes belonging to a rare African lineage and analyze... Present-day humans outside Africa descend mainly from a single expansion out ∼50, 000–70, 000 years ago, but many details of this expansion remain unclear, including the history of the male-specific Y chromosome at this time. Here, we reinvestigate a rare deep-rooting African Y-chromosomal lineage by sequencing the whole genomes of three Nigerian men described in 2003 as carrying haplogroup DE* Y chromosomes, and analyzing them in the context of a calibrated worldwide Y-chromosomal phylogeny. We confirm that these three chromosomes do represent a deep-rooting DE lineage, branching close to the DE bifurcation, but place them on the D branch as an outgroup to all other known D chromosomes, and designate the new lineage D0. We consider three models for the expansion of Y lineages out of Africa ∼50, 000–100, 000 years ago, incorporating migration back to Africa where necessary to explain present-day Y-lineage distributions. Considering both the Y-chromosomal phylogenetic structure incorporating the D0 lineage, and published evidence for modern humans outside Africa, the most favored model involves an origin of the DE lineage within Africa with D0 and E remaining there, and migration out of the three lineages (C, D, and FT) that now form the vast majority of non-African Y chromosomes. The exit took place 50, 300–81, 000 years ago (latest date for FT lineage expansion outside Africa – earliest date for the D/D0 lineage split inside Africa), and most likely 50, 300–59, 400 years ago (considering Neanderthal admixture). This work resolves a long-running debate about Y-chromosomal out-of-Africa/back-to-Africa migrations, and provides insights into the out-of-Africa expansion more generally.